Centering and marginalization in introductory university physics classrooms - Scherr, Rachel E.; Hairston, W. Tali; McKagan, Sarah B.; Miller, Sophie (Frontiers in Education, 2023)
Research-based instructional strategies in physics promote active participation in collaborative activities as a primary means for students to construct understanding. This emphasis is in line with situated learning theory, in which learning is indicated by a student's increasing centrality in a community. In a study of small-group collaborative learning activities in introductory physics classrooms at three different universities, we observe that discussions of physics content are also negotiations of social relations and that full participation is often limited by how students are situated within these social relations: e.g., whether they are centered or marginalized. Our analysis demonstrates that students' ability to actively participate in sensemaking may be limited by their peripheral or marginalized position.